2021
DOI: 10.3390/ijms22179316
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Heat Shock Proteins as Therapeutic Targets and Biomarkers in Fibrosing Interstitial Lung Diseases

Abstract: Interstitial lung diseases (ILDs) include a large number of diseases and causes with variable outcomes often associated with progressive fibrosis. Although each of the individual fibrosing ILDs are rare, collectively, they affect a considerable number of patients, representing a significant burden of disease. Idiopathic pulmonary fibrosis (IPF) is the typical chronic fibrosing ILD associated with progressive decline in lung. Other fibrosing ILDs are often associated with connective tissues diseases, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 126 publications
(138 reference statements)
0
14
0
3
Order By: Relevance
“…IFN- γ was not discovered in the PBMC of patients with other connective tissue diseases (CTD)-ILD. This is due to the fact that IFN- γ production is increased by cit-Hsp90 T lymphocytes specific for RA-ILD [ 19 , 27 , 28 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…IFN- γ was not discovered in the PBMC of patients with other connective tissue diseases (CTD)-ILD. This is due to the fact that IFN- γ production is increased by cit-Hsp90 T lymphocytes specific for RA-ILD [ 19 , 27 , 28 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…The overexpression of αB-crystalline in epithelial cells and fibroblasts increases the nuclear localization of Smad4 by antagonizing its mono-ubiquitination and subsequent nuclear export, thereby promoting the activation of TGF-β downstream target genes. 133 These studies suggest that to facilitate tumor progression, αB-crystallin regulates core components of the EMT program.…”
Section: Alpha B-crystallin (Hspb5)mentioning
confidence: 99%
“…Subsequently, several teams have provided reliable evidence showing that eHSP70 was actually able to activate the immune cells, such as macrophages and monocytes [ 31 , 32 ]. Nowadays, growing evidence has shown that HSPs could be released by various types of cells in several ways, passively or actively, and therefore, the scientific community has fully accepted this phenomenon and more attention has been given to the function of eHSPs in many human diseases [ 19 , 20 , 21 , 33 , 34 ].…”
Section: Hsps Can Be Released Into the Extracellular Milieu And Can B...mentioning
confidence: 99%
“…For the last 20 years, HSPs have been considered to be typical intracellular proteins since the report of the heat shock response and characterization of the 70 kD heat shock proteins. However, growing evidence suggests that HSPs can be released into the extracellular space and blood and that they play essential roles in many human diseases through the modulation of inflammation and immune responses [ 18 , 19 , 20 , 21 , 22 ]. In this review, first, we describe the types of eHSPs, and then discuss the mechanisms of eHSP secretion.…”
Section: Introductionmentioning
confidence: 99%